2015
DOI: 10.1080/13607863.2014.995589
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in Life and depressive symptoms: a person-oriented approach in residential and community-dwelling older adults

Abstract: Similar Meaning in Life-profiles were detected in residential as well as community-dwelling older adults. In both samples, older adults with a High Presence Low Search profile reported less depressive feelings, pointing to the importance of spontaneously experiencing Meaning in Life in this life stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
5
37
1
Order By: Relevance
“…Several studies of community-dwelling older adults have shown that life satisfaction is related to depression [49][50][51]. Additionally, studies reported that the presence of meaning in life is positively linked to health-related quality of life and perceived health [52,53], and Van der Heyden et al showed that the presence of meaning in life is associated with low levels of depressive symptoms [54]. Further, it has been suggested that a sense of meaning derived from daily activities will ultimately bring meaning to life [55].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of community-dwelling older adults have shown that life satisfaction is related to depression [49][50][51]. Additionally, studies reported that the presence of meaning in life is positively linked to health-related quality of life and perceived health [52,53], and Van der Heyden et al showed that the presence of meaning in life is associated with low levels of depressive symptoms [54]. Further, it has been suggested that a sense of meaning derived from daily activities will ultimately bring meaning to life [55].…”
Section: Discussionmentioning
confidence: 99%
“…They have become important topics in contemporary empirical research (Kreitler & Urb anek, 2014;McDonald, Wong & Gingras, 2012;Schnell, 2012), with substantially growing impact (for a review see Heintzelman & King, 2014). Related concepts like meaningfulness, sense of coherence, continuity, and purpose in life have been shown to be associated with better psychological health and functioning, (Haugan, 2014;Hedberg, Brulin, Al ex & Gustafson, 2011;Homan & Boyatzis, 2010;Steger, Mann, Michels & Cooper, 2009;Van der Heyden, Dezutter & Beyers, 2015), better physical health (Czekierda, Banik, Park & Luszczynska, 2017;Roepke, Jayawickreme & Riffle, 2014), and even longevity (Boyle, Barnes, Buchman & Bennett, 2009;Cohen, Bavishi & Rozanski, 2016;Hill & Turiano, 2014;Krause, 2009). Several mechanisms have been proposed to explain the health-promoting effect of meaningfulness.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that in different life situations and phases different dimensions of social togetherness become more central to mental wellbeing. In old age, having opportunities for nurturance and reassurance of worth may increase individuals' experiences of mattering to others and so give meaning to life, thereby reducing the risk for depression (Boman, Gustafson, Häggblom, Santamäki Fischer, & Nygren, 2015;Taylor & Turner, 2001;Van, Dezutter, & Beyers, 2015).…”
Section: Discussionmentioning
confidence: 99%